Pleiotropic effects of Syntaxin16 identified by gene editing in cultured adipocytes - Bremner, Shaun K.; Al Shammari, Woroud S.; Milligan, Roderick S.; Hudson, Brian D.; Sutherland, Calum; Bryant, Nia J.; Gould, Gwyn W. (Frontiers in Cell and Developmental Biology, 2022)
Adipocytes play multiple roles in the regulation of glucose metabolism which rely on the regulation of membrane traffic. These include secretion of adipokines and serving as an energy store. Central to their energy storing function is the ability to increase glucose uptake in response to insulin, mediated through translocation of the facilitative glucose transporter GLUT4 to the cell surface. The trans-Golgi reticulum localized SNARE protein syntaxin 16 (Sx16) has been identified as a key component of the secretory pathway required for insulin-regulated trafficking of GLUT4. We used CRISPR/Cas9 technology to generate 3T3-L1 adipocytes lacking Sx16 to understand the role of the secretory pathway on adipocyte function. GLUT4 mRNA and protein levels were reduced in Sx16 knockout adipocytes and insulin stimulated GLUT4 translocation to the cell surface was reduced. Strikingly, neither basal nor insulin-stimulated glucose transport were affected. By contrast, GLUT1 levels were upregulated in Sx16 knockout cells. Levels of sortilin and insulin regulated aminopeptidase were also increased in Sx16 knockout adipocytes which may indicate an upregulation of an alternative GLUT4 sorting pathway as a compensatory mechanism for the loss of Sx16. In response to chronic insulin stimulation, Sx16 knockout adipocytes exhibit elevated insulin-independent glucose transport and significant alterations in lactate metabolism. We further show that the adipokine secretory pathways are impaired in Sx16 knockout cells. Together this demonstrates a role for Sx16 in the control of glucose transport, the response to elevated insulin, cellular metabolic profiles and adipocytokine secretion.